Buckling of composite perforated plates - Syed Mohamed Ali, Jaffar; Wan Abdullah, Wan Najihah; Aminuddin, Alina (IIUM Press, 2011)
The buckling behaviour of homogeneous and composite plates with cutouts under axial compression is investigated numerically by using ANSYS software. The influence of material orientation and the length to width ratio on the buckling response of the plates is examined.